Bioglass®/chitosan–polycaprolactone bilayered composite scaffolds intended for osteochondral tissue engineering. Issue 12 (26th February 2014) - Yao, Qingqing; Nooeaid, Patcharakamon; Detsch, Rainer; Roether, Judith A.; Dong, Yanming; Goudouri, Ourania‐Menti; Schubert, Dirk W.; Boccaccini, Aldo R.
Abstract Polymer‐coated 45S5 Bioglass®(BG)/chitosan‐polycaprolactone (BG/CS‐PCL) bilayered composite scaffolds were prepared via foam replication and freeze‐drying techniques for application in osteochondral tissue engineering. The CS‐PCL coated and uncoated BG scaffolds were characterized by X‐ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The mechanical properties of the coated scaffolds were significantly improved in comparison to uncoated scaffolds. The bioactivity and biodegradation behavior of scaffolds were studied in simulated body fluid (SBF) for up to 28 days. The interface between the BG scaffold and the polymer coating layer was observed by SEM and a suitable interpenetration of the polymer into the scaffold struts was found. The effects of coated and uncoated BG scaffolds on MG‐63 osteoblast‐like cells were evaluated by cell viability, adhesion and proliferation. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 4510–4518, 2014.